TEKNIK EVAKUASI CEDERA KEPALA PASCA BENCANA KETEPATAN TEKNIK EVAKUASI PADA KORBAN CEDERA KEPALA DALAM MENGURANGI KEJADIAN CEDERA SEKUNDER - Noer Safita; Anindya Atiqah Ristanti; Eka Pramudian Rismayanti; Hitaputra Agung Wardhana (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2019)
Evacuation is an effort to redeploy the victims from the affected area to a safer region to acquire the rescue. Nowadays the lack of a adequate transfer to evacuate disaster victims are the phenomenom which occur in social case spesifically the health workers who get high potency to increase the occurence of secondary injuries to victims. ratio of the results of health research at 2007 and 2013, point out the enhancement of prevalence of head injury from 7,5% being 8,2% and one of  the hospital in Indonesia has held a data which made into a vocal point assert that head injury cases from year to year have increased. The aim of this literature review is to mitigate morbidity and mortality of head injury which go up every year and underpin the health workers to simplify in carry out evacuation to prevent secondary injuries. This literature review was conducted by seeking the electronic databases journal with engage corresponding keywords. The result of the study postulate the victim of injuries particularly post disaster need rapid and appropriate evacuation, assesment and management techniques to rescue suffers live. The treatment carried out when get a head injury is preserve the patients airway, oversee bleeding and preventing shock, immobilizing patient, avert complication and secondary injuries each circumstances which engage in abnormal and dangerous must be given resuscitation. The handling is done alluding to the necessity of ABCDE method by using the START method and mantain stabilization of the cervical technique using the log roll technique.